Information technology in medical education - Kocić, Hristina (Informatica Medica Slovenica, 2013)
The advancements and innovations of information technology offer a number of modes of delivery of medical knowledge and skills. As an education tool, e-learning should satisfy and maintain educational aims, be flexible and enable collaboration and communication between students and teachers. It should be student-oriented and centered towards specific users needs. The virtual patient is a specific clinical examination tool that may be used efficiently for training and assessment. Systematic literature reviews suggest that e-learning is as effective as traditional educational methods, but may offer additional benefits. The article includes a SWOT analysis of e-teaching and e-learning in medical education and identifies the infrastructure required for supporting e-learning within medical education.
Keywords: e-poučevanje; e-učenje; informacijska tehnologija; medicina